Evaluation of the Chemical Properties and Absorption Capacity of Different Manganese Sources using Everted Gut Sacs Technique and Their Effects on the Performance and Immune Response of Broiler Chickens - Farogh Kargar; Hasan Kermanshahi; Ali Javadmanesh; Reza Majidzadeh Heravi (پژوهشهای علوم دامی ایران)
Introduction:Manganese is an essential trace element that acts as an activating component of many crucial enzymes such as alginase and pyruvate carboxylase. It is involved in carbohydrate, lipid, and protein metabolism, as well as in vital biochemical reactions (Hassan et al., 2020). Additionally, manganese serves as a cofactor in the synthesis of chondroitin sulfate and plays a significant role in bone formation in broiler chickens (Mwangi et al., 2019). Moreover, manganese is vital for the antioxidant and immune systems of animals (Patra and Lalhriatpuii, 2020; Wang et al., 2018). In the production of broiler chickens, manganese sources commonly used include inorganic Mn (Mn sulfate, Mn carbonate and Mn oxide) and organic Mn (Mn chelated with amino acid and protein). Inorganic sources of manganese are cheaper, although they have low digestibility (Tufarelli and Laudadio, 2017; Yenice et al., 2015). Organic sources have excellent chemical stability and high absorption efficiency. They have not been widely used in poultry diet due to different quality levels of manufactured products, unpredictable effects and high cost (Tufarelli and Laudadio, 2017; Brooks et al., 2012). Therefore, it is important to assess new sources of manganese that have higher digestibility and lower cost. Manganese hydroxychloride is a group of minerals which solubility in water is minimal, but it becomes more soluble in acidic conditions in intestine (Wang et al., 2011). The purpose of this experiment was to investigate the different levels and sources of manganese in the diet of broiler chickens by investigating their effects on growth performance, immunity, the digestibility of different sources in different solvents, and the digestibility using the technique of Everted Gut Sacs.Materials and Methods: Manganese sulfate, organic manganese, and manganese Hydroxychloride were obtained from Ariana company. In order to measurement of the amount of dry matter and ash, one gram in four repetitions was sampled from each of the sources. They were dried at 105°C for 12 hours and dry matter was calculated through subtraction. Then samples were transferred to the oven at 550°C for 16 hours and their ash content was determined. Finally, they were digested in hydrochloric acid and passed through Whatman filter paper No. 42. After making up to volume with mili-Q water, they were read by an atomic absorption device at a wavelength of 520 to 560 nm (AOAC, 1995; Williams, 1972). In order to evaluate the solubility, three samples (0.1 g) were prepared and dissolved in 100 ml of 2% citric acid, 0.4% hydrochloric acid and deionized water (Watson et al., 1970). For assessment ability to absorb minerals by the technique of Everted Gut Sacs, 180 one-day-old broilers of the Ross 308 commercial strain were fed from one to twenty-one days old with corn and soybean based (2018). On the 22nd day to the 28th day, they were fed with a diet free of manganese and on 29th day, they were starved for one day and night. Chickens were grouped into three treatments with Hydroxychloride, organic and manganese sulfate sources with 6 replications and 10 pieces per replication. Three parts were selected from each replication for the test steps (Feng et al., 2006). Samples prepared from jejunum and ileum in two buffers, Mis-Krebs and Tris-Krebs. In order to determine the relative bioavailability of different manganese sources, an experiment was conducted with 12 treatments included four different levels of manganese (35, 70, 105 and 140 mg/kg) with three different sources including Hydroxychloride, organic and sulfate.Results and Discussion: The highest amount of dry matter of manganese was related to manganese sulfate (99.23%). The lowest was manganese hydroxychloride (92.58%). The highest ash percentage was related to manganese hydroxychloride with 86.14% and the lowest was related to organic manganese with 21.56%. The amount of manganese calculated after testing organic sources, hydroxychloride and sulfate was 5.64, 34.64 and 34.47% respectively. The organic form of manganese had the highest solubility in 2% citric acid and the lowest in deionized water with 96.12 and 34.14%, respectively. Manganese hydroxychloride also had the highest solubility in 2% citric acid solution. Manganese sulfate had the highest solubility in hydrochloric acid and the lowest solubility in deionized water. In general, manganese sulfate had the highest solubility in deionized water compared to the other two sources. Also, the highest solubility of organic manganese in 2% citric acid was 96.12% in the whole experiment. It has been reported in studies that binding minerals with proteins will be a weak chelate and when they are placed in solvents, their chelate breaks easily and dissolve (Cao et al., 2000). The results related to performance traits and primary and secondary response of antibody titer against sheep red blood cells (SRBC) showed that experimental treatments had no significant effect on them. Conclusion: The results showed that the highest solubility of the organic form of manganese was in citric acid (96.12%) and the lowest was in deionized water (34.13%). Manganese hydroxychloride had the highest solubility in 2% citric acid, while manganese sulfate had the highest solubility in 0.4% hydrochloric acid. Overall, manganese exhibited the highest solubility in hydrochloric acid and the lowest in deionized water. The results of the technique of inverted intestinal segments showed that the most absorption of manganese occurs in the ileum, and these results were in line with the results of other researchers who had performed this experiment in vitro and in vivo Among the experimental treatments, the highest absorption in the technique of inverted intestinal segments was related to the organic source of manganese, and the lowest was related to the form of sulfate, 3.25% and 1.99%, respectively. At the end, the use of organic manganese in broiler diet is recommended due to its high absorption level.